2016
DOI: 10.12968/jowc.2016.25.4.210
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of surgical site infection in postoperative patients at a tertiary care centre in India

Abstract: Prevention of SSIs requires a multipronged approach with particular emphasis on optimising preoperative issues, adhering religiously to strict protocols during the intraoperative period and addressing and optimising metabolic and nutritional status in postoperative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 19 publications
6
17
0
1
Order By: Relevance
“…Our findings suggest that postoperative antibiotic prophylaxis does not significantly decrease the likelihood of infection in patients undergoing surgery for facial fractures. However, it is important to emphasize that we were unable to control for a number of key patient characteristics that can increase the risk of infection such as smoking, tobacco use, diabetes, or immunocompromised status . Miles et al also found that the combined use of tobacco and alcohol was more prevalent in patients with infection .…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Our findings suggest that postoperative antibiotic prophylaxis does not significantly decrease the likelihood of infection in patients undergoing surgery for facial fractures. However, it is important to emphasize that we were unable to control for a number of key patient characteristics that can increase the risk of infection such as smoking, tobacco use, diabetes, or immunocompromised status . Miles et al also found that the combined use of tobacco and alcohol was more prevalent in patients with infection .…”
Section: Resultsmentioning
confidence: 82%
“…However, it is important to emphasize that we were unable to control for a number of key patient characteristics that can increase the risk of infection such as smoking, tobacco use, diabetes, or immunocompromised status. 8,21,34,65,70,71 Miles et al also found that the combined use of tobacco and alcohol was more prevalent in patients with infection. 8 Therefore, our conclusions should be considered in light of unique patient characteristics which impact infection rate.…”
Section: Resultsmentioning
confidence: 97%
“…In addition, patients may experience delayed wound healing and be more susceptible to secondary complications, such as bacteraemia. 18,19 Study by Akhter MS et al (2016) 20 showed a SSI rate of 11%. Risk factors associated with a higher incidence of SSI were found to be age (>55 years), diabetes mellitus (especially uncontrolled sugar in the perioperative period), immunocompromised patients (mainly HIV and immunosuppressive therapy patients), surgeon skill (higher in senior professors compared with junior residents), nature of the cases, (emergency surgeries), placement of drains, wound class (highest in dirty wounds), type of closure (multilayer closure), prolonged duration of hospital stay, longer duration of surgery (>2 hours), type of surgery (highest in cholecystectomy).…”
Section: Discussionmentioning
confidence: 97%
“…The highest rates of causative organisms for SSIs found were Staphylococcus aureus, Escherichia coli and Klebsiella ssp. 20 SSIs remain a frequent postoperative complication; developing in 3% to 20% of surgical procedures. 21 The rate of SSI is highly variable depending on the specific operative procedure, with rates that can be even higher depending on the number of risk factors present.…”
Section: Discussionmentioning
confidence: 99%
“…These include antimicrobial sutures and bio‐active sutures such as drug‐eluting and stem cell or growth factor coated sutures. These newly designed sutures represent a response to a critical market, as there has been extensive research done which indicates increased potential for bacterial growth and undesirable inflammatory response when traditional surgical sutures are used …”
Section: Introductionmentioning
confidence: 99%